Looking Back : Taos Indians (Raton, NM Raton Range, 1979)
This photo was featured in the January 11, 1979 copy of the Raton Range. It is depicting two Taos Indians on their horses.
Photo
Master list item #: 73
File location is in the New Mexico file Cabinet
Keywords: Taos Indians; Indian Photographs; Looking Back Series; Newspaper articles -- Raton Range -- Raton, NM